Cholesteryl and diosgenyl glycosteroids: synthesis and characterization of new smectic liquid crystals. (2nd March 2015) - Beaulieu, Rémi; Gottis, Sébastien; Meyer, Claire; Grand, Eric; Deveaux, Virginie; Kovensky, José; Stasik, Imane
Graphical abstract: Highlights: Glycosteroid derivatives obtained by click chemistry. Glycoamphiphile nanorod shape with a separate lipophilic part and hydrophilic part. Glycosteroids which have liquid-crystalline properties (Smectic A phase). Observation of mesophases between 85 and 240 °C. Abstract: While present in large numbers in nature, studies on the physical chemical aspects of glycosteroids are quite rare and focused on cholesterol, and all compounds studied thus far have shown liquid crystalline properties in a narrow temperature range. New glycosteroids composed by cholesterol or diosgenin and different glycosidic moieties have been synthesized here in order to analyze the influence of the structure on the formation of mesophases. These compounds have been studied by crossed polarized optical microscopy. These studies have revealed that these new glycosteroids form Smetic A liquid crystals in a broad temperature range.